Raw data for the manusciprt "Radiance economy in light-emitting diodes" - Zhang, Muyi; Jun, Wu; Kim, Ju-Hyeon; Tian, Zhennan; Yang, Yong; Zhong, Kaiquan; Bai, Sai; Gao, Feng (Linköping University, 2026)
This dataset supports the peer-reviewed manuscript titled "Radiance economy in light-emitting diodes". All data are provided in raw form as acquired directly from the measurement systems, without any secondary processing. The files are compatible with standard data analysis software such as Origin and Excel. The dataset is made available to ensure transparency, reliability, and reproducibility for future related research.
Keywords: Physics; Optics and Photonics; Materials Science; Electronics; Physical Sciences; Fysik